Increasing the Financial Management Skills of Blambangan Raya Perkasa Banyuwangi Shipyard Employees: Peningkatan Kecakapan Pengelolaan Keuangan Karyawan Galangan Kapal Blambangan Raya Perkasa Kabupaten Banyuwangi - Radianto, Denny Oktavina; Gaguk Suhardjito; Rachmad Tri Soelistijono; Priyambodo Nur Ardi Nugroho; Danis Maulana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Indonesian shipping industry still needs to be developed so that the nation's sovereignty over maritime areas and the country's economic growth can be realized. The domestic shipbuilding industry has limitations which result in the number of Indonesian ship fleets being small and uneven. This increases the risk of illegal exploitation of marine resources by ships from foreign countries. Human resource development is still considered to be a very important point in efforts to realize progress in the shipping industry. Therefore, financial management training for shipyard employees in the context of community service will be carried out on a hybrid basis in August 2023. Based on a questionnaire supported by interviews, the participant satisfaction level was obtained at 4.36 on Scale 5. The obstacles that emerged during the training process were distance and time limitations. participants who are company employees who are far from the training provider institution.